2013
DOI: 10.4236/ojmm.2013.34035
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus Infection in Children with Acute Respiratory Infection in Nairobi, Kenya

Abstract: Background: Acute respiratory infection (ARI) is a leading cause of morbidity and mortality in children under five years of age in developing countries with viruses contributing significantly to this problem. The recently identified parvovirus, Human Bocavirus (HBoV), has also been associated with ARI. Objective: To determine the frequency of HBoV in patients with ARI. Materials and Methods: Samples from 125 consenting patients with influenza like illness signs and symptoms were collected. DNA was extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
5
8
0
Order By: Relevance
“…Our results showed that the detection rate of HBoV DNA from NPA samples of children with ALRI was 15.4%, that was in agreement with the results reported by Symekher et al, (2013) that was(16.8%)also it was in agreement with other studies which have had a detection range of between 1.5% -19% (Allander et al, 2007,AlRousan2011) and with another study by Dunn and Miller (2014)that reported, HBoV can be detected to in 1.6 to 21.5% of children with symptoms of respiratory tract infection.…”
Section: Resultssupporting
confidence: 83%
“…Our results showed that the detection rate of HBoV DNA from NPA samples of children with ALRI was 15.4%, that was in agreement with the results reported by Symekher et al, (2013) that was(16.8%)also it was in agreement with other studies which have had a detection range of between 1.5% -19% (Allander et al, 2007,AlRousan2011) and with another study by Dunn and Miller (2014)that reported, HBoV can be detected to in 1.6 to 21.5% of children with symptoms of respiratory tract infection.…”
Section: Resultssupporting
confidence: 83%
“…The high detection rate of HBoV in Africa was consistent with the global increase of HBoV in children less than 5 years of age [4,59]. Children of all age group are most likely to experience HBoV infection as a result of poor sanitation and hygiene practices [59]. The most predominant HBoV subtype identified in Africa was HBoV1, which was detected in all the studies.…”
Section: Resultssupporting
confidence: 66%
“…The prevalence of HBoV in Africa was 13% in individuals suffering from gastroenteritis with and without respiratory tract symptoms. The high detection rate of HBoV in Africa was consistent with the global increase of HBoV in children less than 5 years of age [4,59]. Children of all age group are most likely to experience HBoV infection as a result of poor sanitation and hygiene practices [59].…”
Section: Resultsmentioning
confidence: 67%
“…This seasonal character could be a result of the cold temperature observed in these months of the year as supported by the findings of Erling et al (15). Although not significant, females (59.3%) were found to have a higher prevalence of HBoV in this study (Table 3) among children in South America (13,(16)(17)(18). Children of age group >1 -2 years had the highest detection rate and showed symptoms of highest severity (Table 3).…”
Section: Discussionsupporting
confidence: 78%
“…reported by Symekher et al among Kenyan children (7,(11)(12)(13). This difference could be as a result of sampling strategy, severity of illness in the children recruited and different climates.…”
Section: Discussionmentioning
confidence: 92%